eLingua : Issue 1 : September 2017 / Academy of Language Studies - Chone, Liaw Shun; Ismail, Rushita; Ab. Rahim, Suzana; Razali, Wan Noorli; Mohd Yusuf, Noor Laili; Raja Berahim, Raja Rosila; Bakar, Rofiza Aboo; Lim, Teck Heng; Terng, Hoe Foo; Yih, Mah Boon (Academy of Language Studies, 2017)
1. Majlis Perjumpaan Rektor Bersama Warga 2.0 2. ENGLISH EXIT TEST 2016 Workshop 3. ‘English is Fun’ Workshop 4. Program 10000 Langkah 5. CEFR Training 6. ICEdSS 2016 7. Implementation of iCGPA Trainers-on-trainers (TOT) Workshop at UiTMCPP 8. Language Carnival 2017 9. Khidmat Masyarakat di Rumah Warga Emas Darul Hannan 10. Community Service project at Kampong Perak, Batu Kurau, Perak 11. International Invention & Innovative Competition (InIIC Series 2/2016) 12. Kamus Cendekiawan Bahasa Cina-Bahasa Melayu 13. A Critical Review on the Course Selection for Web-Based Instruction (WBI) Integration 14. Becoming 21st Century Teacher: Transitions of a Teacher’s Role in a Classroom & Sustaining Educators Competencies: Delivery of 21st Century Skills 15. A Review of UiTM Students’ Writing Needs, Writing Problems, and Language Courses Prior to WeCWI’s Course Integration 16. WeCWI: The Third Keynote 17. Lets Learn German 18. What do you see in a mirror?